Carbon surfaces for the oxidative quantification of pravastatin: glassy-carbon vs. screen-printed carbon electrodes - Neves, Marta M. P. S. (2014)
The electrooxidative behavior of pravastatin (PRV) in aqueous media was studied by square-wave voltammetry at a glassycarbon electrode (GCE) and at a screen-printed carbon electrode (SPCE). Maximum peak current intensities in a pH 5.0 buffer were obtained at +1.3 V vs. AgCl/Ag and +1.0 V vs. Ag for the GCE and SPCE surface respectively. Validation of the developed methodologies revealed good performance characteristics and confirmed their applicability to the quantification of PRV in pharmaceutical products, without significant sample pretreatment. A comparative analysis between the two electrode types showed that SPCEs are preferred as an electrode surface because of their higher sensitivity and the elimination of the need to clean the electrode’s surface for its renewal, which frequently is, if not always, the rate-limiting step in voltammetric analysis.